ACTIVE SMOKING AND EXPOSURE TO PASSIVE SMOKING AMONG PREGNANT WOMEN ATTENDING A PRIMARY HEALTH CENTRE IN TEMANGGUNG, INDONESIA - Herlina Mayangsari; Mohammad Afzal Mahmood (The Indonesian Journal of Public Health, 2021)
Smoking during pregnancy threatens the health of mothers and their fetus. There are limited data in Indonesia about risk factors associated with smoking during pregnancy. This study aimed to explore levels of smoking, exposure to second-hand smoke (SHS), and related risk factors among pregnant women. Pregnant women who received antenatal care at the Temanggung Primary Health Centre in Central Java, Indonesia were interviewed face-to-face. They were asked about their smoking status, socio-economic status, pregnancy characteristics, and knowledge about health risks associated with smoking. A total of 80 participants were interviewed, and none of whom reported smoking, but the majority of whom (91.3%) reported exposure to SHS. This is a significant proportion when compared to rates of exposure to SHS recorded in other countries. The age of the mother affected the likelihood of exposure to SHS, with older mothers having a reduced likelihood of SHS exposure (p = 0.013; OR = 0.8; 95% CI = 0.74-0.96). However, the number of pregnancies, ANC visits, level of education, income, and awareness of the health risks associated with smoking were not found to be statistically significant. Although women appeared to be relatively aware of the negative effects associated with smoking and SHS exposure, the high incidence of passive smoking illustrated the challenges encountered by women in avoiding SHS. ANC programme should place greater stress on the dangers of SHS exposure, and also involve the whole family. Additionally, laws should be enacted to restrict or prohibit smoking in public places.Keywords: pregnant women, second-hand smoke, smoking